The essence of legal certainty of land title certificates in the land registration publication system in Indonesia - Vivin Astharyna Harysart; Suyanto Suyanto (Journal of Law Science, 2024)
The problem of legal certainty regarding land title certificates, which are a type of land registration in Indonesia, has persistently presented significant obstacles to society, because In Indonesia, the prevailing system of publication is characterized as negative, despite the presence of certain positive aspects. However, the validity of certificates attesting to these rights can be subject to disputes and the state is unable to assure the accuracy of both physical and legal information. This study involves normative legal research from statutory sources, conceptual, and philosophical approaches. The results of research into the nature of legal certainty regarding land rights certificates cannot yet be given to individuals or organizations that own land rights in Indonesia sustained as a result of the absence of a proactive land registration publication system.